Safety and Effectiveness of Percutaneous Needle Fasciotomy for Dupuytren's Disease in the Palm - Mansha, Muhammad; Flynn, Darren; Stothard, John (Journal of Hand and Microsurgery, 2017)
Purpose Percutaneous needle fasciotomy is performed in the authors' department to treat Dupuytren's contracture at metacarpophalangeal joints. This study aimed to establish its safety and efficacy, compared with standard fasciectomy.Materials and Methods All patients who had this procedure performed over the study period were sent the validated British Society for Surgery of the Hand (BSSH) postal questionnaire assessing surgical outcome. Hand function and disability were assessed using the Patient Evaluation Measure (PEM).Results Statistically significant improvement was achieved in Dupuytren's contracture at the mean follow-up of 15 months (SD +/− 10). Approximately 97% of the fingers fully corrected at surgery remain straight. Recurrence rate was 2.2% among fully corrected fingers. However, 2 (40%) out of 5 partially corrected fingers had recurrence. No complication of any kind was noted and no antibiotics used. Hand function was measured using PEM score correlated well with the residual contracture.Conclusion Percutaneous needle fasciotomy is safe, effective, has very low complication rates, and yields comparable results to standard fasciectomy.
Keywords: Dupuytren's disease; fasciotomy; percutaneous needle fasciotomy; surgical treatment